The Influence Of Work Motivation And Work Environment On Employee Performance In The Non-Formal Education Unit (SPNF SKB) Of South Bengkulu District - Mawarni, Hasana; Soleh, Ahmad; Nurzam, Nurzam (Jurnal Ekonomi, Manajemen, Akuntansi, 2025)
The purpose of this study was to determine whether there was an influence of Work Motivation and work environment on employee performance in Non-Formal Education Units (SPNF SKB) of South Bengkulu Regency. The method in this study used Validity Test, Reliability Test, Multiple Linear Regression Analysis, Determination Coefficient and hypothesis test. This type of research uses quantitative research. The number of samples in this study were all ASN Employees (SPNF SKB) of South Bengkulu Regency, totaling 33 ASN employees. The results of the multiple linear regression analysis are the equation: Y = 9.969 + 0.402 X1 + 0.376 X2 +e, this illustrates a positive regression direction, meaning that the motivation variables (X1) and Work Environment (X2) have a positive influence on Employee Performance (Y) in the Non-Formal Education Unit (SPNF SKB) of South Bengkulu Regency. The value of the coefficient of determination from the calculation results using SPSS can be seen from the coefficient of determination of R square of 0.738. This means that the value of Motivation (X1) and the value of the work environment (X2) affect employee performance (Y) by 73.8% while the remaining 26.2% is influenced by other variables not examined in the study.